State Responsibility for Nickel Mining Activities (Case Study of Environmental Damage in Southeast Sulawesi Province) - Indra Gunawan (PT Syamilah Literasi Islami, 2024)
This study aims to explore the state's responsibility related to nickel mining activities, which are seen as a moral bond regulated in the constitution between the state and its people. The focus of this study is on the environmental impacts caused by nickel mining activities in Southeast Sulawesi Province, which is known as one of the nickel industry centers in Indonesia. Environmental damage that occurs in this region is the main focus, considering the important role of the state in ensuring the preservation of nature and the welfare of the affected community. Through a normative legal approach, this study examines state responsibility using three main methods: a conceptual approach, an analysis of relevant laws and regulations, and case studies of several incidents related to environmental damage due to nickel mining. From the results of the study, it was found that the problems arising from nickel mining activities in Southeast Sulawesi emphasize the need for clearer and more assertive state responsibility in dealing with environmental damage. The state should bear full responsibility for the negative consequences of mining activities, especially since existing regulations are often not effective enough in protecting the environment and local communities from the negative impacts caused.